Fracture healing. The evolution of our understanding - Perren, S. M (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2008)
Our understanding of fracture healing has undergone an evolution over many decades with continuous improvement of fracture treatment. Solid union is a precondition of restoring the function of a fractured bone. The goal of the early treatment of the fracture was focussed upon enabling solid union in acceptable alignment of the fracture. This was achieved with reduction followed by application of external splints. The function of the articulations was often troubled by long lasting and extensive external immobilization, which required physiotherapy that lasted longer than bone union. The surgical reduction and stabilization aimed at early recovery of movement of the articulations and maintenance of the function of the soft tissues and blood supply. The AO group initiated 1958 by Maurice E. Müller and his colleagues prioritized the recovery of limb function and propagated precise reduction and fixation using mainly compression. Absolute stability of fixation, achieved using implants, allowed to move the articulations very early without pain, while the fracture united solidly. After such treatment the implants could not be removed before 1 1/2 to 2 years without risking increased incidence of re-fracture. This was in sharp contrast to the fact that after conservative treatment the bone was solidly united after 2 to 3 months. The analysis of this situation revealed that internal remodelling after absolutely stable fixation did not recognize the presence of the fracture. Primary healing, therefore, is not a healing in the strict sense of the word but a side effect of internal removal of necrotic bone. To maintain early function of the limb and stimulate the healing process the so called biological internal fixation was developed. It combines minimal surgical trauma, acceptable rather than precise reduction and flexible fixation usually achieved with so called internal fixateurs. Flexibility of mind and of tools aims at safe and early healing with full recovery of function and minimal risk of biological complications.
Keywords: Fracture Healing; Fracture Fixation; lidé; hojení fraktur; fixace fraktury; Humans